2020
DOI: 10.1111/ajd.13267
|View full text |Cite
|
Sign up to set email alerts
|

Randomised, controlled, double‐blind study of combination therapy of oral tranexamic acid and topical hydroquinone in the treatment of melasma

Abstract: Background/Objectives: Melasma is a common pigmentary disorder for which oral tranexamic acid has shown some efficacy in previous studies. The aim of this study was to assess the effectiveness of oral tranexamic acid in combination with hydroquinone cream in the treatment of melasma. Methods: Subjects with moderate-to-severe melasma were enrolled. Group A received hydroquinone 4% cream, sunscreen and oral tranexamic acid, while Group B received hydroquinone 4% cream, sunscreen and placebo capsules for 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…There was a 42% reduction of mMASI as compared to baseline in Group A vs. 4.7% in Group B after 3 months of treatment. Results of this study was in favor of more effectiveness of combination of oral TXA with topical HQ as compared to topical HQ alone 23 similar to our study.…”
Section: > 3 Months Duration Of Melasmasupporting
confidence: 89%
“…There was a 42% reduction of mMASI as compared to baseline in Group A vs. 4.7% in Group B after 3 months of treatment. Results of this study was in favor of more effectiveness of combination of oral TXA with topical HQ as compared to topical HQ alone 23 similar to our study.…”
Section: > 3 Months Duration Of Melasmasupporting
confidence: 89%
“…Among the 24 studies, 1383 patients were included. Eight studies [14][15][16][17][18][19][20][21] evaluated the efficacy and safety of oral TXA, four studies [22][23][24][25] evaluated the efficacy and safety of intradermal TXA, and twelve studies evaluated the efficacy and safety of topical TXA. 5,[26][27][28][29][30][31][32][33][34][35][36] In the study by Tawfic SO, 30 topical and intradermal TXA administration routes were adopted in the treatment arm; thus, the study was analysed separately.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…We retrieved 86 studies from three databases, among which 24 studies published between 2013 and 2020 were finally eligible for inclusion 5,14–36 (Figure 1). Detailed information on the studies included is presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…21 Shihab et al conducted a randomized, controlled, double-blind study of 50 Indonesian females with moderate or severe melasma which showed participants treated with 500 mg/day TXA and 4% hydroquinone cream had a more significant reduction in mMASI at 3 and 6 months than those treated only with 4% hydroquinone. 22 In a prospective, randomized controlled trial conducted in Nepal, 130 melasma patients were treated with 500 mg TXA daily in conjunction with routine topical hydroquinone and sunscreen for 3 months. When compared with those treated solely with routine topical measures, patients who also received oral TXA demonstrated a significantly lower mean MASI score at both 8 and 12 weeks.…”
Section: Resultsmentioning
confidence: 99%